Functional Expression and Characterization of Tetrachloroethene Dehalogenase From Geobacter sp. - Nakamura, Ryuki; Obata, Tomohiro; Nojima, Ryota; Hashimoto, Yohey; Noguchi, Keiichi; Ogawa, Takahiro; Yohda, Masafumi (Frontiers in Microbiology, 2018)
Reductive dehalogenase (RDase) consists of two parts, RdhA and RdhB. RdhA is the catalytic subunit, harboring a cobalamin cofactor and two Fe-S clusters. RdhA is anchored to the cytoplasmic membrane via the membrane anchoring subunit, RdhB. There are many genes encoding RDases in the genome of organohalide-respiring bacteria, including Dehalococcoides spp. However, most genes have not been functionally characterized. Biochemical studies on RDases have been hampered by difficulties encountered in their expression and purification. In this study, we have expressed, purified and characterized RdhA of RDase for tetrachloroethene from Geobacter sp (PceA). PceA was expressed as a fusion protein with a trigger factor tag in E. coli. PceA was purified and denatured in aerobic condition. Subsequently, this protein was refolded in the presence of FeCl3, Na2S and cobalamin in anaerobic condition. The reconstituted PceA exhibited dechlorination ability for tetrachloroethene. UV–Vis spectroscopy has shown that it contains cobalamin and FeS clusters. Since this method requires anaerobic manipulation only in the reconstituting process and has a relatively high yield, it will enable further biochemical studies of RDases.